Algebraic properties of finite switchboard state machine - Ebas, Nur Ain; Amir Hamzah, Nor Shamsidah; Jacob, Kavikumar; Othman, Fatin Shahirah; Rusiman, Mohd Saifullah; Ahmad, Noor’ani; Abdul Kahar, Rosmila (2018)
A finite switchboard state machine is a specialized finite state machine. The algebraic approach of finite switchboard state machine is still lacking in literature. In this paper, we applied the algebraic approach of finite switchboard state machine and study its related properties. Real life examples of the applications are given by discussing the algebraic properties used.